Pelayanan Publik: Kajian Pendekatan menurut Perspektif Islam - Jailani Jailani (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Ar-Raniry, 2013)
Public service is all service activities undertaken by public service providers as addressing the needs of service recipients as well as the implementation of the provisions of the legislation. Public can also be interpreted as many people or too general. The principle of transparency means a unit of public services should be open, easy and accessible to all who need and provided adequately and easy to understand. The principle of accountability; Conditional; Participatory; Equal rights; Simplicity; Clarity; Certainty time; accuracy; Security; responsibility; Completeness means and Keprasaranaan; Then access; discipline, politeness and friendliness, as well as comfort. Service approach is Islam that is the approach teleology and deontology approach